2020
DOI: 10.1109/access.2020.3022062
|View full text |Cite
|
Sign up to set email alerts
|

SVP: Sinusoidal Viewport Prediction for 360-Degree Video Streaming

Abstract: The rapid growth of user expectations and network technologies has proliferated the service needs of 360-degree video streaming. In the light of the unprecedented bitrates required to deliver entire 360-degree videos, tile-based streaming, which associates viewport and non-viewport tiles with different qualities, has emerged as a promising way to facilitate 360-degree video streaming in practice. Existing work on viewport prediction primarily targets prediction accuracy, which potentially gives rise to excessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Nasrabadi et al [5] proposed a clustering-based method to estimate the user's future viewport. Jiang et al [6] interpreted the original rotation amount as a sine value to reduce the prediction error of the yaw direction. ese trajectory-based methods may be used in live because they only require real-time data from the current video session.…”
Section: Viewport Predictionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nasrabadi et al [5] proposed a clustering-based method to estimate the user's future viewport. Jiang et al [6] interpreted the original rotation amount as a sine value to reduce the prediction error of the yaw direction. ese trajectory-based methods may be used in live because they only require real-time data from the current video session.…”
Section: Viewport Predictionmentioning
confidence: 99%
“…e most advanced VR streaming research mainly focuses on viewport prediction [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. e existing solutions [1,[11][12][13] suggest prefetching all the tiles of each segment, and higher quality of prefetching predicts the tiles in the viewport.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality of the viewport-based streaming highly depends on the accuracy of the viewport prediction. For accurate viewport prediction, there are non-learning-based [35]- [39] and learning-based [40]- [43] prediction methods. The most existing studies on the non-learning-based viewport prediction utilize a regression curve obtained from the past head movement, such as linear regression (LR) [35], [38], [39] and weighted LR (WLR) [36], [37].…”
Section: Viewport Predictionmentioning
confidence: 99%
“…In the learning-based prediction methods, [40] used saliency map prediction based on orientation data of multiple users and [41] further adopted the recurrent neural network (RNN)-based long short-term memory (LSTM) model to predict future viewport movement from both the saliency map and past head orientation. Some studies [42], [43] discuss the effect of the LR-based and deeplearning-based methods on the viewport prediction. They found that the difference of the prediction accuracy between both methods is slight.…”
Section: Viewport Predictionmentioning
confidence: 99%